Comments on the paper "Global stabilisation of periodic linear systems by bounded controls with applications to spacecraft magnetic attitude control". (April 2018) - Lovera, Marco
Abstract: This note contains comments on the paper Zhou (2015a), with specific reference to: the fact that the result in Theorem 3 of the paper is not new but actually goes back to the early 60s; a few comments on the actual scope and applicability of the method proposed in the paper; some corrections to the literature review provided in the paper.